Protection of intellectual property in cyberspace - Menon, Shailaja (Authorspress, 2003)
Contents of material: Introduction. Cyber intrusion. Impact of cyber crimes and problems in investigation. Protection of intellectual property in cyberspace. Laws governing cyber piracy in India and the international treaties.